Priming Benih Padi (Oryza sativa L.) dengan Zn untuk Meningkatkan Vigor Bibit pada Cekaman Terendam - Sulaiman, Sulaiman; Suwignyo, Rujito Agus; Hasmeda, Mery; Wijaya, Andi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 2016)
Seed priming has been widely used to improve seedling vigor of several crops  such as corn, wheat, and rice. Seed priming with zinc to increase seedling tolerance on submergence stress had never been evaluated. The objective of this research was to identify agronomical and physiological characteristics of several rice genotypes during seedling stage at submergence stress following zinc priming treatment. This research used factorial randomized block design with three replications. The first factor was rice genotypes and second factor was zinc solution of ZnSO4.7H2O. Seeds were soaked with Zn solution at different concentrations namely 0, 2.5, dan 5.0 mM respectively for 24 hours. After that the seeds were germinated on soil media in side the plastic box. Fourteen days-old seedling were submerged in water for 5 days and then return to normal condition for recovery. Parameters being observed included seedling dry weight, shoot carbohydrate, and leaves chlorophyl which were measured after 10 days of recovery. Seedling height was measured once a week from 2nd to 4th week. Results showed that intolerant genotypes to submergence stress grew faster but seedling dry weight, shoot carbohydrate and leaves chlorophyll content were lower compared to those tolerant genotypes. Local and national varieties which were not tolerant to submergence stress could be improved by priming treatment with 5.0mM zinc.Keywords: abiotic-stress, seeds- priming